PRINCIPLES OF TEACHING IN THE ELECTRONICS EDUCATION - SERAFIN, Cestmir (Trends in education, 2015)
Didactic process in the electronic learning is a process that is not according to the subjective desire and discretion of the teacher. Neither the learner has mastered electrical knowledge systematically, if it will proceed spontaneously and passively. The teaching process must be broken on the basis of objective regularities, which are generally worded in such didactic principles. The contribution deals with the definition of these principles in the context of electrical education. It also includes the concept of epistemological procedures as a significant feature of the educational process of this education.
Keywords: Didactic principles; Subject didactics; electrical engineering; epistemological procedures.